Laminar airflow versus turbulent airflow in simulated total hip arthroplasty: measurements of colony-forming units, particles, and energy consumption. (September 2021) - Marsault, L.V.; Ravn, C.; Overgaard, A.; Frich, L.H.; Olsen, M.; Anstensrud, T.; Nielsen, J.; Overgaard, S.
Summary: Background: The optimal type of ventilation in operating theatres for joint arthroplasty has been debated for decades. Recently, the World Health Organization changed its recommendations based on articles that have since been criticized. The economic and environmental impact of ventilation is also currently an important research topic but has not been well investigated. Aim: To compare how large, high-volume, laminar airflow (LAF) and turbulent airflow (TAF) ventilation systems perform during standardized simulated total hip arthroplasty (THA), as they pertain to colony-forming units (cfu), particle counts, and energy consumption. Methods: Two identical operating theatres were used to perform simulated THA. The only difference was that one was equipped with LAF and the other with TAF. Cfu and particles were collected from key points in the operating theatre, and energy was measured for each simulation. Thirty-two simulations were done in total. Findings: LAF had significantly reduced cfu and particle count when compared with TAF, at both 100% and 50% air influx. Furthermore, it was shown that lowering the air influx by 50% in LAF did not significantly affect cfu or particles, although reducing the fresh air influx from 100% to 50% significantly lowered the energy consumption. Most simulations in TAF did not meet the cleanroom requirements. Conclusion: Cfu were significantly lower in LAF at both 100% and 50% air influx. It is possible to reduce fresh air influx in LAF operating theatres by 50%, significantly reducing energy consumption, while still maintaining cfu and particle counts below the ISO classification threshold required for THA surgery.